Directed differentiation and direct reprogramming: Applying stem cell technologies to hearing research. (30th December 2020) - Roccio, Marta
Abstract: Hearing loss is the most widely spread sensory disorder in our society. In the majority of cases, it is caused by the loss or malfunctioning of cells in the cochlea: the mechanosensory hair cells, which act as primary sound receptors, and the connecting auditory neurons of the spiral ganglion, which relay the signal to upper brain centers. In contrast to other vertebrates, where damage to the hearing organ can be repaired through the activity of resident cells, acting as tissue progenitors, in mammals, sensory cell damage or loss is irreversible. The understanding of gene and cellular functions, through analysis of different animal models, has helped to identify causes of disease and possible targets for hearing restoration. Translation of these findings to novel therapeutics is, however, hindered by the lack of cellular assays, based on human sensory cells, to evaluate the conservation of molecular pathways across species and the efficacy of novel therapeutic strategies. In the last decade, stem cell technologies enabled to generate human sensory cell types in vitro, providing novel tools to study human inner ear biology, model disease, and validate therapeutics. This review focuses specifically on two technologies: directed differentiation of pluripotent stem cells and direct reprogramming of somatic cell types to sensory hair cells and neurons. Recent development in the field are discussed as well as how these tools could be implemented to become routinely adopted experimental models for hearing research. Abstract : This review analyzes two stem cell technologies: directed differentiation of pluripotent stem cell and direct reprogramming of somatic cells as methods to derive human specific inner ear cell types. In vitro platforms using organoids or monolayer cultures provide novel tools to validate therapeutic strategies. Among these, gene editing, gene therapy, drug‐based therapy, and cell replacement strategies. Potential applications are discussed.